The Effectiveness of Problem-Based Learning on Syarh Mukhtashar Jiddan Through Critical Thinking Approach/Fa‘aliyyah al-Ta‘allum al-Qa’im ‘ala al-Musykilah li-Syarkh Mukhtasar Jiddan Bina’an ‘ala Manhaj al-Tafkir al-Naqdi - Sofiyah, Dzakirotus; Inayah, Inayah; Fatimatuzzahro; Waesama-ae Waemamu (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2025)
This study examined the effectiveness of problem-based learning on the Syarh Mukhtashar Jiddan book, employing a critical thinking approach, among 20 students at Pondok Pesantren Fadhlul Fadhlan in Semarang. The research method employed was a quasi-experimental one-group pre-test post-test design. The data analysis used a paired sample t-test, involving both pre-test and post-test to assess the improvement in learning outcomes and measure changes in the students' critical thinking skills after the implementation of problem-based learning. Based on the data analysis, the average score difference between the pre-test and post-test is -3.40000, with a t-test value of -8.643, indicating a statistically significant improvement. These findings suggested that the intervention provided was effective in improving the students' learning outcomes and their engagement with Arabic grammar (Qawāʿid Naḥwīyah). The study contributed to Islamic education research by highlighting the relevance of learner-centered approaches such as problem-based learning, especially when dealing with classical texts. It also underscored the importance of integrating critical thinking into traditional curriculum in pesantren to enhance deeper understanding and student autonomy.